Reuse Upcycling Sebagai Wujud Peduli Lingkungan Warga Sekolah di SD Islam Cendekia Kota Bukittinggi - Salsa Agra Siwi; Nefilinda Nefilinda (Yayasan Pendidikan Penelitian Pengabdian Algero, 2022)
The purpose of implementing service activities is to provide knowledge, skills and experience about reuse upcycling as a form of environmental care for school residents to reduce waste in the school environment, this is also a contributor to waste. Also consider reducing waste, it is also necessary to pay attention to the aesthetic side and have good usability. The method used in this community service activity is the lecture method and practice/demonstration. The lecture method was carried out to deliver material on environmental impacts related to the amount of waste in the form of used cardboard, used flannel, leftover yarn, used plastic bags, and used tires. An explanation of how to make upcycling reuse to utilize used goods. The method of practice/demonstration is carried out to provide examples of the process of making reuse upcycling starting from making a toga garden and making a reading garden. The results of these training activities are (1) The implementation of training activities on making a toga garden using flower pots that can still be utilized by painting and using used tires as a garden medium in the school yard as a reuse upcycle, (2) School residents are trained in gardening read by reusing upcycling using used cardboard, used flannel, leftover yarn, used plastic bags, and old tires to extend the life with high creativity. Based on the evaluation of the process, 100% of participants' attendance during the training was met. Meanwhile, based on the results of the practice, 80% of the participants were able to make a toga garden and a reading garden well, have good usability and creativity.